2013
DOI: 10.3109/00016489.2012.762117
|View full text |Cite
|
Sign up to set email alerts
|

Vibrant Soundbridge in congenital osseous atresia: multicenter study of 12 patients with osseous atresia

Abstract: The mean functional gain obtained for all patients evaluated was 62 dB at 0.5 kHz, 60 dB at 1 kHz, 48.3 dB at 2 kHz, and 50.8 dB at 4 kHz. The mean functional gain for all frequencies evaluated was 55.1 dB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 12 publications
1
17
0
4
Order By: Relevance
“…[11][12][13][14] It is wise to not combine VSB implantation with reconstructive surgery of the auricle or the external ear canal at the same time because the latter suffers from a significant rate of complications, which may harm the functionality of the VSB. However, for those patients suffering from pure conductive hearing loss, bone-anchored hearing aids are the first option because they are easier to apply, not putting the middle ear structures and inner ear function at risk during implantation and because they yield similar functional results.…”
Section: Vibrant Soundbridge Rehabilitationmentioning
confidence: 99%
“…[11][12][13][14] It is wise to not combine VSB implantation with reconstructive surgery of the auricle or the external ear canal at the same time because the latter suffers from a significant rate of complications, which may harm the functionality of the VSB. However, for those patients suffering from pure conductive hearing loss, bone-anchored hearing aids are the first option because they are easier to apply, not putting the middle ear structures and inner ear function at risk during implantation and because they yield similar functional results.…”
Section: Vibrant Soundbridge Rehabilitationmentioning
confidence: 99%
“…In another new study from Argentina [28], an even higher functional gain is showed with 55.1 dB HL in 12 patients with osseous atresia.…”
Section: Risks and Benefitsmentioning
confidence: 99%
“…Some authors suggested the outcome was better with FMT placed over oval window and stapes crura [28], while the others suggested that there was no significant difference [30].…”
Section: Risks and Benefitsmentioning
confidence: 99%
“…A casuística deste estudo foi composta por 20 indivíduos, sendo 10 normo-ouvintes e 10 usuários de VSB com atresia de orelha bilateral e perda auditiva (G1). Comparando com outros estudos sobre o tema, este número não pode ser considerado pequeno, visto que a maioria dos trabalhos foi realizada com estudo de caso e casuísticas compostas por até 12 indivíduos Kiefer et al, 2006;Frenzel et al, 2009;Nicollas;Bernadeschi et al;Colletti et al, 2011; Stankeviciute; Petrulionis; Sarasty, 2012;Pujol;Zernotti et al, 2013;Yang et al, 2014;Mondelli et al;Zhao et al, 2016;Célérier et al;Leinung et al, 2017). Além de ser o primeiro estudo realizado com o objetivo proposto nesta população, os participantes do G1 apresentaram atresia de orelha bilateral, o que deve ser considerado, visto que a maior parte dos casos de atresia de orelha é unilateral (Schuknecht, 1989;Jovankovičová et al, 2015).…”
Section: Discussionunclassified
“…Os estudos realizados em indivíduos com atresia de orelha mostram melhora nos limiares audiométricos e nos resultados dos testes de percepção auditiva da fala realizados com o uso do processador de fala após a cirurgia Kiefer;Arnold;Staudenmaier, 2006;Frenzel et al, 2009;Nicollas;Bernadeschi et al;Colletti et al, 2011; Lesinskas; Stankeviciute; Petrulionis; Sarasty, 2012;Pujol;Zernotti et al, 2013;McKinnon et al;Yang et al, 2014;Ernst et al;Zhao et al, 2016;Célérier et al;Leinung et al, 2017), e maior benefício, em questionário de satisfação, comparado ao uso do aparelho de condução óssea anterior ao VSB (Leinung et al, 2017). (Ponton et al, 1996;Sharma et al, 1997;McGee, 1999); deste modo, o processo de mielinização se completaria nesta fase.…”
Section: Introductionunclassified